2013
DOI: 10.1016/j.desal.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of PPEES/chitosan composite nanofiltration membrane

Abstract: Composite membrane having chitosan (CH) as the active layer supported on Poly(1,4phenylene ether ether sulfone) (PPEES) membrane was synthesized in the current study. The chitosan layer was crosslinked by glutaraldehyde in two different concentrations. The scanning electron microscopic images and hydraulic permeability coefficient revealed the ultrafiltration (UF) nature of the neat PPEES membrane. This was used as a new support material for the casting of chitosan layer in order to get composite membranes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Both the glutaraldehyde dosage and temperature were higher than those used in other studies (13 g of quaternary chitosan salt to 10 mL 25% w/v glutaraldehyde at room temperature). In addition, Shenvi et al . reported that the 79.9° contact angle for PPEES–chitosan composite membranes crosslinked by 0.6% glutaraldehyde was higher than the 73.2° contact angle of composite membranes crosslinked by 0.2% glutaraldehyde.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the glutaraldehyde dosage and temperature were higher than those used in other studies (13 g of quaternary chitosan salt to 10 mL 25% w/v glutaraldehyde at room temperature). In addition, Shenvi et al . reported that the 79.9° contact angle for PPEES–chitosan composite membranes crosslinked by 0.6% glutaraldehyde was higher than the 73.2° contact angle of composite membranes crosslinked by 0.2% glutaraldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, no obvious difference on the surface pore structure was found from the SEM images of the membranes. Usually, a higher affinity between membrane materials and water in a coagulation bath promotes nonsolvent influx upon immersion in the coagulation bath when other kinetic and thermodynamic factors are fixed; this favors the formation of a porous surface and fingerlike bulk in the membrane . Maybe, the uniform distribution of CQS grains in the casting solution and the small ratio of CQS in the casting dope did not change the affinity between the membrane materials and water in the coagulation bath.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, many efforts have been done to substitute petro-based polymers by biodegradable ones with similar properties in a low cost and effective manner [4]. According to the previous studies, applying biodegradable polymers in membrane preparation is mostly contributed to chitosan [5][6][7][8][9] and after that poly (lactic acid) [10][11][12]. Starch is a natural, popular and cheap biodegradable polymer produced in abundance from many renewable resources.…”
Section: Introductionmentioning
confidence: 99%
“…Nano‐filtration membranes play a prominent role in the removal of toxic heavy metals, and more so the thin‐film composite (TFC) membranes, which are an important class of nano‐filtration membranes . The TFC membranes, often used in separation processes, have a dense, thin, and selective skin layer and a micro‐porous support layer prepared from various polymeric materials, namely polysulfone (PSf), polyether sulfone, polyurethane, polyacrylonitrile, and polyvinyl difluoride …”
Section: Introductionmentioning
confidence: 99%
“…[13] The TFC membranes, often used in separation processes, have ad ense, thin, and selective skin layer and am icro-porous support layer prepared from various polymericm aterials, [10] namely polysulfone( PSf), polyether sulfone, polyurethane, polyacrylonitrile, and polyvinyl difluoride. [14] Chitosan (CS) has recently shown itsi mpact in membrane separation. CS is an ontoxic, odorless, antibacterial, biocompatible, and biodegradable hetero-polysaccharide obtained by the N-deacetylation of an atural polymer chitin, [15,16] and serves as av ery good material for membrane preparation.…”
Section: Introductionmentioning
confidence: 99%